The Effect Of Heating Temperature On The Hardness, Microstructure And V-Bending Spring Back Results On Commercial Steel Plate - Asep Ruchiyat; Muh Anhar; Yusuf Yusuf; Betti Ses Eka Polonia (Journal of Applied Engineering and Technological Science (JAETS), 2019)
The need for low carbon steel plate sheets with relatively thin thickness measurements in Indonesia is currently quite high, especially in supporting the automotive industry, the electronics industry, the food industry, beverages, and household appliances. To fulfill this, raw materials for low carbon steel plate sheets that have high formability and are not easily cracked in critical areas of the desired model are required. For this reason, research on the effect of temperature variations in heat treatment on hardness, microstructure and spring back of V-bending results on steel plates with a plate thickness of 0.8 mm. The research method used was a laboratory experimental method. The heat treatment is carried out with temperature variations of 710, 820 and 9300C with a holding time of 60 minutes. Tests carried out on specimens are hardness testing, microstructure testing, and spring back V-bending results on steel plates. The results of this study indicate a decrease in the spring back angle where the smallest spring back angle in the bending process is on the 9300C plate which is 1,040. The value of the hardness results from V-bending has increased significantly. The increase in the value of hardness because the plate has an atom shift or dislocation by shear stress (slip) due to plastic deformation on the plate. The highest hardness value is on the 7100C plate which is 154.67 HV or has an increase of 14,291% of the pre-bending plate. The lowest hardness value is on the 9300C plate which is 125.33 HV, its hardness increases 4.4% against the pre-bending plate. Heat treatment also causes changes in the microstructure of the plates from the process of regulation and reshaping of crystals to the growth of new grains which have implications for changes in mechanical properties and formability of the workpiece.